Student experiences and satisfaction with a novel clerkship patient scheduling. Issue 1 (1st January 2020) - Oberhelman, Sara; Boswell, Chris; Jensen, Teresa; Swartz, Daniel; Bruhl, Elliot; O'Brien, Marcia; Angstman, Kurt
ABSTRACT: Background : Outpatient primary care clerkships are an important part of medical students' education.Traditional clerkships usually partner a student with a single preceptor in that physician's clinic. However, it can be quite difficult for the preceptor to balance the educational needs of the students, the expectations of the patients and the organizational demands of the clinic practice.Objective : An innovative scheduling model (named "Patients as Teachers" [PAT] clinic) was developed as part of our third-year Family Medicine clerkship. The goal was to increase the students' opportunities for independence and improve their satisfaction without negatively impacting the flow of the clinic or patient satisfaction.Design : The third-year medical students spent part of their clerkship working in the PAT clinic and part of the time working with an individual preceptor in that preceptor's clinic in the traditional, usual fashion (PAU clinic-precepting as usual). The students completed patient-logs regarding the patients they saw and their level of participation. They also completed a voluntary survey regarding their experiences.Results : Students performed more independent interviews (90.3 vs 59.0%) and independent exams (96.2 vs 63.3%) in the PAT clinic than while working with their traditional preceptor (both p<0.01). Students were highly satisfied with the experience with 89.5% stating they would recommend it and 87.7% finding the PAT clinic to be an equal or superior experience to the PAU experience.Conclusions : Using a combination of time in the PAT clinic and time with a one on one preceptor in the usual fashion was successful in increasing opportunities for student autonomy and achieving a high level of student satisfaction in our third-year Family Medicine clerkship. Additional opportunities for innovative scheduling could be considered for meeting a variety of clerkship and clinic needs.